A novel risk assessment method for advanced and environmentally friendly construction technologies integrating RBM and I-OPA - Yunbin Sun; Zaohong Zhou; Qiang Li; Hongjun He (Alexandria Engineering Journal)
The execution of advanced construction technologies during an organization’s digital transformation presents formidable challenges but valuable environmental performance to construction projects. Navigating the uncertainty inherent in decision-making within risk assessment is a particularly intricate aspect of these challenges. To this end, the paper proposes an innovative risk assessment method that integrates RBM and I-OPA for advanced construction technology. First, RBM is utilized to establish a comprehensive risk indicator system, identifying key risk factors. Next On the basis of risk identification, the I-OPA model is developed to prioritize these risks and quantify their weights, employing interval weight lengths and threshold metrics to analyze decision-making uncertainty. Conclusively, the efficacy of the proposed method is ascertained through a data reliability analysis, leading to the proposal of tailored risk management strategies. The validity of this novel method is demonstrated through the risk assessment of the project utilizing an advanced and environmentally friendly Prefabricated auxiliary Steel platform Drilling Technology(PSDT). The results indicate that the policy implementation orientation (17.2%) and the level of safety consciousness (11.6%) are identified as the most critical risk factors within the construction organization’s safety management. Moreover, the drilling construction process of the project is ascertained to be the highest risk level. Furthermore, the method affords a pivotal reference for the formulation of safety management strategies and sustainable construction management.